Sensitivity to Copper and Phosphite of Phytophthora Species Associated with Ink Diseases of Chestnut - Coelho, Valentim (2005)
Phytophthora cinnamomi (23 isolates) and P. cambivora (3 isolates), isolated from chestnut showing ink disease symptoms or from soil near dead roots of chestnut trees were tested to copper and phosphite sensitivity. Isolates were characterized using an amended agar assay. EC50 values (copper (or phosphite) concentration inhibiting mycelial growth of the pathogen by 50%) for each isolate were calculated by plotting probit percentage inhibition against log10 active ingredient (a.i.) concentration. EC50 values of copper ranged from 0.043×10-3 to 2.025×10-3 M in P. cinnamomi and 1.970×10-3 to 4.603×10-3 M in P. cambivora. EC50 values of phosphite ranged from 2.99 to 172.39 μg ml-1 in P. cinnamomi and 47.23 to 237.25 μg ml-1 in P. cambivora. This study may contribute to access the potential utility of these a.i. for managing ink disease of chestnut and to use in the future as benchmark for baseline sensitivity.